Efektivitas Model Praktik Kolaborasi Interprofesional (PKIP) Tenaga Kesehatan Terhadap Kinerja Pelayanan Kesehatan Rumah - Prayetni Prayetni; Ni Made Riasmini; Bondan Palestin; Tri Prabowo (Poltekkes Kemenkes Jakarta III, 2018)
Primary health care is an essential service that can be accepted by individuals, families in the community. Family health services face clients with actual, potential or potential health problems that are complex using biopsikososiospiritual Cooperation between health workers is needed so that the health services provided are effective and efficient. This research is operational research with qualitative and quantitative methods. Qualitative research uses descriptive design and quantitative research using Cross Sectional design. This study was designed to develop a model / form of interprofessional cooperation practice of health workers that is validated through statistical tests. The research will be carried out by two people, the first model develops and the two effective models of PKIP on the performance of health services and the quality of services to clients. The research sample used in the quantitative research was purposive sampling with a total of 155 people. To test the model using a structured equation model test (SEM). The results of the study showed all variables of Recognition among Professionals of Health Workers, Self-Confidence, Role of Health Responsibility, Leadership, Communication, Team Work, forming PKIP models that were in accordance with the influence, and connecting to the performance of home health services.